1879 Tenn. Pub. Acts 135- 36, ch. 46, §§ 1-6 - (:unkn) unknown (My University, 1879)
Made the sale, offer of sale, or importation into the state belt pistols, pocket pistols, revolver, or any other kind of pistols except Army or Navy pistols a misdemeanor.
Keywords: COMMERCIAL SALES REGULATION